2008
DOI: 10.1080/15502280802225234
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Contributing to Subsidence Above Gas Reservoirs and its Application to a Case Study

Abstract: This paper aims to demonstrate that capillary effects and structural collapse can not be ruled out as significant factors in the development of subsidence occurring above gas fields. These phenomena provide sound explanations for continuing surface settlements when reservoir pore pressures stabilize and for additional settlements occurring even after the end of gas production. Conventional subsidence models fail to simulate this settlement behavior. Capillary effects also explain the lower rock compressibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…In Figure 6 in the periods [1982][1983][1984][1985][1986][1986][1987][1988][1989][1990][1991][1992] in 1986-1992 and in 1992-1996 periods the peak softens until the 1999-2005 period where the top has almost leveled out. This behaviour up to 1999 has first been evidenced in Menin et al (2008) and is here confirmed. The explanation put 1982, 1986, 1992BENCHMARKS 1999, 2005 Depleted gas fields forward, as mentioned above, is water inflow in the reservoir to fill the pressure gap left from exploitation: the degree of saturation increases in fact, starting from the borders, destroying capillary forces, speeding up reservoir compaction and ensuing subsidence.…”
Section: Ec 323supporting
confidence: 83%
See 2 more Smart Citations
“…In Figure 6 in the periods [1982][1983][1984][1985][1986][1986][1987][1988][1989][1990][1991][1992] in 1986-1992 and in 1992-1996 periods the peak softens until the 1999-2005 period where the top has almost leveled out. This behaviour up to 1999 has first been evidenced in Menin et al (2008) and is here confirmed. The explanation put 1982, 1986, 1992BENCHMARKS 1999, 2005 Depleted gas fields forward, as mentioned above, is water inflow in the reservoir to fill the pressure gap left from exploitation: the degree of saturation increases in fact, starting from the borders, destroying capillary forces, speeding up reservoir compaction and ensuing subsidence.…”
Section: Ec 323supporting
confidence: 83%
“…These variations correspond to measured values (see Menin et al 2008). For sake of completeness, the subsidence resulting from the simulation for the whole period 1955-2005 is depicted in Figure 12, for a point on the surface above the border of the reservoir.…”
Section: Depleted Gas Fieldssupporting
confidence: 72%
See 1 more Smart Citation
“…Throughout the dataset, point elevations decreased, mainly in the period 1950-1970, when the slope of the straight lines was greater. This effect was simultaneous with or slightly delayed with respect to the most intense phase of methane extraction [37] [39] [47] [52]. In the last period, 1970-2005, after extraction ceased, the phenomenon was still not exhausted [61].…”
Section: Available Data and Gps Measurementsmentioning
confidence: 99%
“…Proper distinction between saturated and unsaturated states is not only relevant for a more comprehensive representation of the occurrence and magnitude of plastic volumetric compression (e.g. [3,5,6,10,20,28,33,44,65,66,76]) but also for a more reliable prediction of shear strength (e.g. [11,12,22,48,73,79]).…”
Section: Introductionmentioning
confidence: 99%